Features of addictive personality - Krainikov, Eduard; Prokopovich, Eugeniy; Balanyuk, Аlona (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
We surveyed 50 people between the ages of 18 and 25, most of respondents are college students. We used the following assessment tools: SMOL (abbreviated adaptation of MMPI), Heim's test for coping strategies, Mendelevich's methodic, Michigan Alcohol Test (MAST), Urgent Dependence Questionnaire in Shibko's adaptation. Respondents show some signs of predisposition, or even a clear presence of addictive behavior. Choosing a way to escape from reality was a cultural phenomenon, that is, the choice of an addictive agent is more dictated by advertising, public opinion, and art products. This data confirms the close direct relationship between alcohol dependence (according to MAST) and psychopathy — a correlation coefficient of 0.27. According to the regression analysis, the data of this scale strongly depend on the indicators of the hysteria scale (P-value = 0.01). This indicates that expressing alcohol and the consequences of such abuse can make a person protesting, uncomfortable, and seeking to exaggerate their problems and attract attention. The results of the study confirmed the literature data about self-centered, depressive, and anxious fetures of addictive personality. We can assume that the higher the emotional lability, anxiety and depressive personality, the greater the likelihood of addiction to computer games. It is worth noting that this dependency is different from the other vivid virtual world, which gives the person the opportunity to hide in him from the troubles. For people with adaptation disorders and computer addiction, clinical manifestations of anxiety and depression, severe depressive and anxiety episodes are common; high levels of situational and personal anxiety, excessive nervous and mental stress. That is, we can conclude that both computer addiction and gaming addiction are strongly linked to anxiety and depression. We assume that these dependencies are very closely related and that it is difficult to draw a clear boundary. In addition to health problems, psychoactive substance use, and addiction to procedural addiction, it causes significant social and economic damage to individuals and society as a whole.
Keywords: addiction; addictive behavior; urgent dependence; psychoactive substances